STRATEGI KOMUNIKASI PT. PEGADAIAN (PERSERO) CABANG PANAM PEKANBARU DALAM MEMPROMOSIKAN TABUNGAN EMAS KEPADA NASABAH - Manurung, Kezia; Susanti, Hevi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
PT. Pegadaian employees as communicators have a large role in promoting gold savings in PT. Pegadaian Panam Branch to a wide audience. In carrying out his duties, there is a need for ability and expertise in promoting gold savings and having interesting ways of communication and appearance in order to be able to influence prospective customers. In this script, the author discusses how the communication strategy carried out by PT. Pegadaian in promoting gold savings. The purpose of this study is to find out how communicators strategy, messaging strategy, media selection strategy, and audience selection strategy in promoting gold savings at PT. Pegadaian Panam Branch of Pekanbaru. This research method uses qualitative research methods. This research informant consists of 5 people, namely Branch Leadership, Asistent Marketing Officer, Customer Relations Officer and 2 Customers to support this research. Data collection techniques consist of interviews, observations and documentation, while data analysis techniques use communication strategy models. Data validity checking techniques use extended participation and tringulation. Based on the results of the research that the author has done, the results of the research to identify the problem are that the first communicator in promoting gold savings is that all employees participate but the main key as communicators are employees of the marketing division. And a communicator must have credibility and appeal. The message has 2 forms of messages, namely verbal messages and nonverbal messages. Verbal messages, namely Personal Selling through face to face. And written verbal messages such as brochures, banners, social media. Meanwhile, nonverbal messages can be seen from body language, facial expressions, tone of voice and simple language. The media used offline is face to face which is the main media and print media are brochures, banners/banners. While online, namely electronic media and social media such as WhatsApp, Instagram and Tiktok. Selection of the audience determines the target audience in promoting gold savings ranging from 17-60 years old, and tends to be millennials because millennials currently spend more time and income in places that are not clear, such as hanging out in cafes Keywords: PT. Pegadaian, Gold Savings, Communication Strategy, Promotion